Entre palavras e imagens: o acontecimento de 11 de setembro nas revistas Veja e Carta Capital : a arquitetura do imaginário social sobre o terrorismo - Barion, Carolina de Oliveira Françoso [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The inquiries that we went through to do this study are the ones that related to the eminent democratization of media instruments into the contemporary society. To elaborate it, we considered the idea that the day-by-day life, into the contemporary view, is constantly conducted by the possibility of transforming any happening into news, and then being thrown to the public. This way, the knowledge build-up become based on the information acquisition by individuals, and this ones are produced by the media through the news. Thinking about this perspective, we concerned about understanding how the media discourse, while pedagogical language, takes part into the social imaginary build-up about terrorism based on the cover news from the magazines Carta Capital and Veja, the ones that had shown the September 11th happening. To work on this, we were based on the Foucault discourse and also on the information paradigm, proposed by Castells. Based on the reports about the happening, we tried to understand the proposed discourse by the mentioned magazines about the configuration of a collective view about the terrorism, which we called social imaginary, by Díaz‟s perspective. Our aim here is to discuss the texts produced by a cultural industry dependent of a market logic in an accelerated production and also by the images produced and shared by specialized agencies to several publications, from different sectors and publishers. This way, we believe it is possible to establish a connection among the buildup social imaginary about terrorism, based on a collective view about the subject, the information in the presented texts and also the images that showed the September 11th happening, in 2001. We propose to understand the September 11th as a happening based on the Foucault Theory, which understands it as a historical rupture (or novelty ), and also as a historical regularity: as all the historical novelty brings it into regularity,...

As indagações que nos atravessaram para a realização desse estudo são aquelas que se ligam à eminente democratização dos instrumentos midiáticos na sociedade contemporânea. Para a elaboração do mesmo, levamos em conta a ideia de que a vida cotidiana, na contemporaneidade, é meandrada constantemente pela possibilidade de transformação de qualquer acontecimento em notícia, a qual é atirada no público. Assim, a própria construção do conhecimento passa a basear-se na aquisição de informações pelos indivíduos, as quais são produzidas pela mídia, por meio da notícia. Pensando a partir dessa perspectiva, nos preocupamos em compreender como o discurso midiático, enquanto linguagem pedagógica, participa da construção de um imaginário social sobre o terrorismo, a partir das reportagens de capa das revistas Carta Capital e Veja, que noticiaram o acontecimento de 11 de setembro. Para essa empreitada, buscamos base na perspectiva foucaultiana de discurso e na configuração de um paradigma da informação, proposto por Castells. Baseando-nos nas reportagens que noticiaram o acontecimento, buscamos compreender o discurso proposto pelas revistas em questão para a configuração de uma visão coletiva sobre o terrorismo, que aqui chamamos imaginário social, na perspectiva de Díaz. Cabe-nos, assim, discutir a respeito dos textos, produzidos por uma indústria cultural dependente de uma lógica de mercado baseada em uma produção cada vez mais acelerada e das imagens, produzidas e repassadas pelas agências especializadas a diversas publicações, de diferentes editoras e segmentos. Dessa forma, entendemos ser possível estabelecer relações entre a construção de um imaginário social sobre o terrorismo, baseado em uma visão coletiva a respeito do assunto, e as informações presentes nos textos e nas imagens que noticiaram o acontecimento de 11 de setembro, no ano de 2001. Propomos, ainda...
Keywords: Education; Educação; Terrorismo - Cobertura jornalística; Análise do discurso; Percepção social; Imaginario